German in the Classroom: Development of a Learning Medium to Support Students in the German Lesson Preparation Course - Ambarwati Rizka Wardhani (Universitas Negeri Malang, 2020)
This research and development pursues the aim to develop an instructional medium in the form of an Android-based application named “Deutsch im Klassenzimmer“ that is intended for German students of Universitas Negeri Malang, who attend the course Unterrichtsvorbereitung Deutsch and will undertake a student teaching internship in high schools. The application serves as a phrase book that contains german classroom phrases and their translation in Bahasa that can be used by German teachers during teaching. The development will be guided by the ADDIE concept from Branch, validated by media design and material experts, and will be tested to 40 students. The data will be obtained through indirect observation and questionnaire and will be analysed using qualitative descriptive analysis. The result of the observation indicates that the phrases that are used by the subjects are learned from the application. The result of the survey shows that the subjects consider the application to be good, helpful, and easily accessed. It is stated, that the application facilitates the learning process and the subjects will continue using the application during student teaching internship.